A new species of the genus Conostigmus Dahlbom 1858 (Hymenoptera: Ceraphronoidea: Megaspilidae) from India - Ghosh, Amit Kumar; Kumar, Vikas; Rameshkumar, Anandhan; Tyagi, Kaomud (Zootaxa, 2025)
A new species, Conostigmus khonomaensis sp. nov., is described from Nagaland, India. Two male specimens were collected by yellow pan traps from the Khonoma village in Nagaland. Moreover, this is the second species of the genus Conostigmus reported from India. An identification key to the two Indian species of Conostigmus is also provided.